(3TYQ YHOGdYRjR NhLI (B: s (3OQGSI afjI (B/ s - (3EHQGgje YeQ GdeMGFdjs; (3YhV Ydj GdZHGQj (B: s ((3GdbGgQI (B: s (3EHQGgje YeQ GdeMGFdj (B: s, 2012)
(3JJfGhd gPg GdOQGSI GdYdejI HGdYQV h GdJMdjd fJGL hGMO ef CHQR GdTYQGA GdSYhOjjf GdeYGUQjf gh GdTGYQ GdOcJhQ YHOGdYRjR eMjj GdOjf NhLI(B. (3h JgOa GdOQGSI Edi QUO GdedGeM GdafjI h GdNUGFU GdCSdhHjI GdJj JJejR HgG GdcJGHI GdEHOGYjI GdTYQjI ddTGYQ YHOGdYRjR NhLI HUaJg CMO GdTYQGA GdSYhOjjf GdeYGUQjf(B. (3h SJJhba GdOQGSI YfO YOO ef fUhU NhLI GdTYQjI QGUOI CHQR edGeMgG GdafjI(B: (3h bGQFI ddfUhU bQGAI afjI efWdbI ef GdCOhGJ GdfbOjI GdeYQhaI GdJj ef NdGdgG jecf SHQ CZhGQ GdfJGL GdTYQj ddTGYQ NhLI (B: (3h SJbhe GdOQGSI Ydi GdefgL GdGSJbQGFj GdhUaj GdJMdjdjs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GddZI GdYQHjI hBOGHgGs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdKbGaI h GdTYQs; (3GdTYQ GdYQHi s; (3YHOGdYRjR NhLI s